2020
DOI: 10.1021/acs.est.0c01587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Momentum Wakes behind Moving Vehicles and Dispersion of Vehicle Emissions Using Near-Roadway Measurements

Abstract: A parameterization of initial vertical dispersion coefficient (σ z,init) was developed for incorporation into California line source dispersion model, version 4 (CALINE4) and AMS/EPA regulatory model (AERMOD) to better predict pollutant concentrations near roadways. The momentum wake theory of moving vehicles indicates that both vehicle-induced turbulence (VIT) and dispersion occur in the vehicle wake. Based on a literature review, it is postulated that σ z,init near roadways can be estimated using a “wake are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The Transition Phase includes the effect of thermal turbulence, vehicular turbulence, and atmospheric turbulence. This phase is assumed from the downwind distances of 6.5 m to 50 m. The value of 50 m will depend on the type of vehicles on the highway and could be as high as 150 m for large trucks, as pointed by Yu et al [37]; c.…”
Section: Turbulence Parametrizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Transition Phase includes the effect of thermal turbulence, vehicular turbulence, and atmospheric turbulence. This phase is assumed from the downwind distances of 6.5 m to 50 m. The value of 50 m will depend on the type of vehicles on the highway and could be as high as 150 m for large trucks, as pointed by Yu et al [37]; c.…”
Section: Turbulence Parametrizationmentioning
confidence: 99%
“…The values of σ z0 obtained from the above four procedures for a test case are shown in Table 2 using the width of the road as 3.5 m. The wind velocity considered was 1.4 m/s, the wind angle concerning the road was taken as 90 • , and the average height of the vehicle was H = 1.65 m. The effective wake length was considered as 9.3 m, and the vehicle density on the roadway was 0.125 vehicles/m. [37,[40][41][42].…”
Section: Turbulence Parametrizationmentioning
confidence: 99%
See 1 more Smart Citation
“…By conducting field measurement , and simulation, researchers concluded that VIT and RIT dominate on-road turbulent mixing, while ABLT dominates turbulent mixing at downwind locations (near-roadway). Researchers also found that HDDVs produce much larger and stronger turbulent mixing than light-duty gasoline vehicles (LDGVs) , and the strength of the turbulent mixing was more correlated to HDDVs than to LDGVs. ,, Besides effects from turbulent mixing, a recent study found that the NO 2 /NO x ratios measured at curbside were less sensitive to ambient background O 3 , which is probability because of the limited amount of available O 3 (not titrated) in the curbside environment.…”
Section: Introductionmentioning
confidence: 99%
“…The ventilation within the canyon may be suppressed [9], and vortices can leave dead zones with stagnant air [2]. Sometimes, slow-moving, heavy traffic along the roads at the canyon bottom exhausts large amounts of primary pollutants and generates turbulence [10]. Typically, ozone (O 3 ) is a limiting factor for the oxidation of nitric oxide (NO) to nitrogen dioxide (NO 2 ) [11], making the contribution of primary NO 2 important.…”
Section: Introductionmentioning
confidence: 99%